The Application of Blockchain Technology with Unmanned Aerial Vehicles (UAVs) for Plant Protection in Thailand - Sampaothong, Sonthya; Punyawattoe, Pruetthichat (Arts of Management Journal, 2024)
This article explores the potential applications of blockchain technology in conjunction with unmanned aerial vehicles (UAVs), commonly known as drones, for plant protection in Thailand. The agricultural sector faces numerous challenges from insect pests, plant diseases, and environmental factors that significantly impact crop production. Advanced technologies can be employed to develop innovative solutions for enhancing monitoring, detection, and prevention in an efficient, accurate, and timely manner. Blockchain enables the creation of a decentralized, transparent, and immutable record-keeping system to store data transactions throughout the agricultural supply chain. When combined with smart contracts, blockchain enhances the trustworthiness of data exchange among stakeholders. This paper discusses the integration of UAV technology on a blockchain-based platform for applications in Thailand, including pest surveillance, targeted pesticide spraying, farm management, supply chain traceability, and agricultural insurance. The benefits and limitations of combining these two emerging technologies are considered. However, further research and collaboration between the public and private sectors are necessary for Thailand to fully realize the potential of these technologies, leading to increased agricultural competitiveness in the future.